Practical Panarchy for Adaptive Water Governance Linking Law to Social-Ecological Resilience (Springer International Publishing, 2018)
This book presents the results of an interdisciplinary project that examined how law, policy and ecological dynamics influence the governance of regional scale water based social-ecological systems in the United States and Australia. The volume explores the obstacles and opportunities for governance that is capable of management, adaptation, and transformation in these regional social-ecological systems as they respond to accelerating environmental change. With the onset of the Anthropocene, global and regional changes in biophysical inputs to these systems will challenge their capacity to respond while maintaining functions of water supply, flood control, hydropower production, water quality, and biodiversity. Governance lies at the heart of the capacity of these systems to meet these challenges. Assessment of water basins in the United States and Australia indicates that state-centric governance of these complex and dynamic social-environmental systems is evolving to a more complex, diverse, and complex array public and private arrangements. In this process, three challenges emerge for water governance to become adaptive to environmental change. First, is the need for legal reform to remove barriers to adaptive governance by authorizing government agencies to prepare for windows of opportunity through adaptive planning, and to institutionalize the results of innovative solutions that arise once a window opens. Second, is the need for legal reform to give government agencies the authority to facilitate and participate in adaptive management and governance. This must be accompanied by parallel legal reform to assure that engagement of private and economic actors and the increase in governmental flexibility does not destabilize basin economies or come at the expense of legitimacy, accountability, equity, and justice. Third, development of means to continually assess thresholds and resilience of social-ecological systems and the adaptive capacity of their current governance to structure actions at multiple scales. The massive investment in water infrastructure on the river basins studied has improved the agricultural, urban and economic sectors, largely at the cost of other social and environmental values. Today the infrastructure is aging and in need of substantial investment for those benefits to continue and adapt to ongoing environmental changes. The renewal of institutions and heavily engineered water systems also presents the opportunity to modernize these systems to address inequity and align with the values and objectives of the 21st century. Creative approaches are needed to transform and modernize water governance that increases the capacity of these water-based social-ecological systems to innovate, adapt, and learn, will provide the tools needed to navigate an uncertain future.